Quantitative Identification of the Water Resistance Capacity of Composite Strata in Mining Coal Seam Floors - Xinyi Wang; Fang Li; Qi Wang; Bo Chen; Yu Zou; Bo Zhang (Geofluids)
In coal seam mining, the water resistance of the floor composite strata is the key to determining whether water disaster occurs or not and to formulating water control countermeasures. Taking the Pingdingshan Coalfield No. 8 mine and Shoushan mine as the research objects, the thickness ratio of plastic brittle rock, core recovery rate, thickness of effective aquiclude, fault complexity, composite compressive strength, and equivalent water resistance coefficient were selected as the index factors. The comprehensive weight of each index factor was determined by using the entropy weight theory. The water resistance of the J16-17 coal seam floor composite rock in the study area was quantitatively evaluated using the fuzzy variable set mathematical model and was divided into five grades: extremely weak, weak, medium, strong, and very strong. The results show that the J16-17 coal floor composite rock layers with strong and very strong water resistance areas account for 23.64% of the total area, the medium areas account for 58.26%, and the weak and extremely weak areas account for 18.1%. These results provide support for the accurate assessment of water inrush hazards of a coal floor.